2019
DOI: 10.26858/jppk.v5i2.10930
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, academic motivation, self-regulated learning and academic achievement

Abstract: This study aims to empirically prove that the relationship between selfefficacy, academic motivation, self-regulated learning and academic achievement. In addition, empirically proved the mediating role of self-regulated learning on self-efficacy, academic motivation and student achievement. This study used quantitative expansive method. The sample of this study was 246 students of an Islamic senior high school recruited using census technique; thus, the entire population was used as the sample of the study. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Cobb (2003) said that selfregulated learning is influenced by many factors, including self-efficacy, motivation, and goals. According to Alafgani and Purwandari (2019), self-efficacy, motivation, and learning goals possessed by students are positively related to self-regulated learning. Self-efficacy that consistently exists in students can have a positive effect on self-regulation (Bradley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cobb (2003) said that selfregulated learning is influenced by many factors, including self-efficacy, motivation, and goals. According to Alafgani and Purwandari (2019), self-efficacy, motivation, and learning goals possessed by students are positively related to self-regulated learning. Self-efficacy that consistently exists in students can have a positive effect on self-regulation (Bradley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It affects how students believe they can apply the skills and abilities they have to learning tasks (Bong and Skaalvik, 2002). But academic efficacy can also be negatively associated with academic achievement when students are overconfident or underconfident of their abilities (Alafgani and Purwandari, 2019). Some studies also indicate reciprocal effects between prior achievement and self-efficacy (Olivier et al, 2019), with prior achievement having a stronger effect (Talsma et al, 2018;Ansong et al, 2019;Sorjonen and Melin, 2023), and few studies have found weak effects of self-efficacy on student achievement (Ansong et al, 2019;Li et al, 2023).…”
Section: Self-e Cacy and Achievementmentioning
confidence: 99%
“…Learning media can be both traditional and modern which are very effective in increasing student learning motivation (Bye, Pushkar, & Conway, 2007;Parkerson, 2015). Empowering instructional media effectively can be the best way to improve student performance in understanding and mastering all the math materials provided by teachers in class (Alafgani & Purwandari, 2019;Hakim, Sa'ud, Komariah, & Sunaengsih, 2018;Mulyana et al, 2021). Learning media increases motivation, motivation increases school culture, and a good school culture can improve student learning outcomes (Heckhausen & Heckhausen, 2018;Thoonen, Sleegers, Oort, Peetsma, & Geijsel, 2014).…”
Section: Figure 2 Students' Learning Motivation Trendlinesmentioning
confidence: 99%